Antiemetic treatment of hyperemesis gravidarum in 1,064 Norwegian women and the impact of European warning on metoclopramide: a retrospective cohort study 2002-2019 - Hilde Erdal; Lone Holst; Kristine Heitmann; Jone Trovik (BMC, 2022)
Abstract Background Women suffering from severe nausea and vomiting during pregnancy, hyperemesis gravidarum, have poor quality of life and increased risk of potentially fatal maternal and fetal complications. There is increasing and reassuring knowledge about safety of antiemetics in pregnancy. In 2013, the European Medical Agency (EMA) issued a warning on metoclopramide limiting treatment to maximum five days. Metoclopramide was the most used antiemetic in pregnancy at the time the warning was implemented in the Norwegian hyperemesis guidelines (2014). We aimed at describing changes in the treatment of hyperemesis over time, including changes associated with the EMA warning. Methods Retrospective chart review of all women hospitalized for hyperemesis gravidarum with metabolic disturbances between 01/Jan/2002 and 31/Dec/2019 at a university hospital serving nearly 10% of the pregnant population in Norway. Time-series analysis described changes over time and interrupted time series analysis quantified changes in treatment and clinical outcomes related to the EMA warning. Results In total, 1,064 women (1.2% of the birthing population) were included. The use of meclizine, prochlorperazine, and ondansetron increased during 2002-2019. This led to a yearly increase in the percentage of women using any antiemetic of 1.5% (95%CI 0.6; 2.4) pre-hospital, 0.6% (95%CI 0.2; 1.1) during hospitalization, and 2.6% (95%CI 1.3; 3.8) at discharge. Overall, only 50% of the women received antiemetics pre-hospital. Following the EMA warning, prehospital use of metoclopramide dropped by 30% (95%CI 25; 36), while use of any antiemetic pre-hospital dropped by 20% (95%CI 5.7; 34). In timely association, we observed a decrease in gestational age (-3.8 days, 98.75%CI 0.6; 7.1) at first admission, as well as indication of increased rate of termination of pregnancy with an absolute increase of 4.8% (98.75%CI 0.9; 8.7) in 2014. Conclusion During 2002-2019, the overall use of antiemetics in treatment of hyperemesis increased. The EMA-warning on metoclopramide in 2013 temporarily limited pre-hospital antiemetic provision associated with hospitalization at lower gestational length and indication of an increase in termination of pregnancy.